Inkonsistensi Prinsip Ragam Tulis pada Aplikasi Pesan Instan WhatsApp - Nicky Rosadi; Yulian Dinihari (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2022)
This study aims to discuss the inconsistency of the principle of writing style that occurs in the WhatsApp instant messaging application. The method used in this study is a qualitative method using descriptive analysis techniques. The object in this study is the text of the conversation on the WhatsApp instant messaging application which is taken randomly and then documented in the form of images so that the chat can be recorded visually. The results of the study show that, there is an inconsistency in the principle of writing style in the WhatsApp instant messaging application which causes this form of variety to not be fully said to be a type of writing. This inconsistency is seen at the time of opening the chat, as much as 100% of the existing data, the sender of the message uses a written variety with intact principles. However, when a reply is received and a conversation occurs, 55,7% of the data shows that the principle of writing style is no longer fully applied. It was found that the sender of the message answered by using a sentence structure that was incomplete and there was an omission of elements, both subject, predicate, object, and description. In addition, it was also found 36% data showing that in the delivery, the sender of the message sometimes uses certain emoticons as an effort to build context, which in the spoken variety is usually accommodated by gestures and facial expressions. In this regard, the researcher concludes that the variety that appears in the WhatsApp instant messaging application can no longer be said to be a written variety. Due to the inconsistency of applying the principles of written and spoken variety, the authors suggest that the variety that appears in this instant messaging application is called the inlis variety.